Model Konseling Tazkiyah Kognitif-Islami Bagi Mahasiswa Muslim Yang Mengalami Kecemasan Dan Krisis Makna Hidup - Azizah Binti Abd Ghani (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2026)
This article aims to develop an integrative Islamic Counseling model that addresses anxiety and existential crisis among Muslim university students. Contemporary psychological issues among students are closely related to cognitive distortions and loss of spiritual meaning. Cognitive Behavioral Therapy (CBT) has been empirically proven effective in reducing anxiety; however, it often lacks a spiritual dimension. Using a conceptual qualitative method and an istiqrā’ (inductive) approach, this study integrates CBT principles with the Islamic concept of tazkiyah al-nafs. Data were analyzed through critical analysis of psychological theories and Islamic primary sources. The proposed Tazkiyah Cognitive-Islamic Counseling Model emphasizes cognitive restructuring through muhasabah, spiritual strengthening through dhikr and prayer, and behavioral change through righteous deeds. This model is expected to contribute to the development of holistic Islamic counseling practices relevant to contemporary mental health challenges